Amputation of an Extra-root with an Endodontic Lesion in an Invaginated Vital Maxillary Lateral Incisor: A Rare Case with Seven-year Follow-up - Ã‡alÄ±ÅŸkan, Mehmet Kemal; Asgary, Saeed; Tekin, UÄŸur; GÃ¼neri, Pelin (Iranian Endodontic Journal, 2016)
The developmental abnormality of tooth resulting from the infolding of enamel/dentin into the root is called dens invaginatus. Management of such cases is usually challenging due to the morphological complexity of root canal system. This report presents a rare treatment protocol of a clinical case of Oehler’s type III dens invaginatus combined with an endodontic lesion in a vital maxillary lateral incisor. Access to the endodontic lesion located between the central and lateral incisors was achieved by reflection of a full mucoperiosteal flap. Granulomatous tissue as well as aberrant root was removed and the surface of the root and adjacent coronal region were reshaped. Three years later, the patient was orthodontically treated. Seven years after completion of surgical/orthodontic management, the tooth remained asymptomatic and functional with normal periodontium/vital pulp. Radiographically, the healing of the lesion was observed. Actually, vitality of the invaginated tooth and communication between the invagination and the root canal were the most important factors in determining such minimally invasive treatment protocol. Depending on the anatomy of the root canal system, surgical amputation of an invaginated root can be performed to achieve a successful outcome in Oehler’s type III dens invaginatus cases, even though it is associated with apical periodontitis. Keywords: Apical Periodontitis; Dens Invaginatus; Endodontic Therapy; Lateral Incisor; Periradicular Surgery